Preparation of Cefalexin/MCM-41 Composite Material and Its Controlled Release Property - Hu, Wei-Hua; Zhai, Qing-Zhou; Li, De-Kun (Asian Journal of Chemistry, 2012)
MCM-41 mesoporous material was prepared by hydrothermal synthesis and a cefalexin/ MCM-41 composite material was prepared by impregnation method. Tetrahydrated ammonium molybdate was used for to detect the concentration of drugs by the spectrophotometric method before and after loading. The detection of cefalexin loading capacity in the MCM-41 mesoporous material was 696.5 mg/g. Before and after the loading, MCM-41 molecular sieve and its composite material sample were characterized by chemical analysis, Fourier transform infrared spectroscopy, powder X-ray diffraction, scanning electron microscopy, transmission electron microscopy and 77 K low temperature N2 adsorption-desorption. A diameter of the composite material was 333 ± 5 nm of fibrous grains. The release law of cefalexin/MCM-41 in the simulated body fluid, gastric and intestinal fluid was investigated. The maximum cumulative release in simulated body fluid was 99.2 % at 15 h. The maximum cumulative release in simulated gastric juice was 38.7 % at 6 h and in simulated intestinal fluid the maximum cumulative release rate of 47.9 % was achieved at 7 h.